Mantle flow through Drake Passage with the gravity tomography data - Greku, R. H.; Litvinov, D. A.; Greku, T. R. (Ukrainian Antarctic Journal, 2015)
Drake Passage opening is associated with important milestones of the Earth’s history: formation of the Antarctic Circumpolar Current, initiation of the cryogenic zone on the Antarctica continent and effect of this sphere on global climate. Movement of water masses from the Pacific Ocean to the Atlantic Ocean via Drake Passage is only a consequence of geodynamic processes of the lithospheric plates’ shifting and mantle flows of the Earth’s interior. The aim of our work is to model of deep structure and distribution of dense inhomogeneities, as well as to restore geodynamic processes in the lithosphere and mantle of the Drake Passage’s transition zone. Our gravity tomography method was used for modeling (Greku et al., 2009). It is based on realization of the Professor Moritz’s theoretical approach that equipotential surfaces of the Earth coincide with surfaces of constant density, as well as using of his algorithm for determination of harmonic density anomalies by spherical harmonics of the gravitational potential. The method includes following procedures: determination of depths for disturbing masses; determination of density for disturbing masses by the EGM 2008 geoid model. Tomographic models have been created as the vertical cross-sections and lateral slices (maps) for different depths. The work of Barker (2001) on tectonic evolution of the Scotia Sea in view of the Alvarez’s hypothesis (Alvarez, 1982) on the driving mechanism for mantle flow was used for interpretation and analysis of the tomographic models. The crosssection along latitude of 58°S is showing mantle flow on the sub-lithospheric layer of the Pacific Ocean at the depth of 183 km at a distance of 2000 km to the westward from the Shackleton Fracture Zone. Mantle flow loses integrity (continuity) at shallower depths due to interaction with others bodies and it is represented as fragments. Mantle flow’s possible penetrations into the Scotia Sea’s subcrustal layers are marked at depths of 10 km and 3 km. Lateral expansions of mantle flow are shown at the depths of 183 km, 77 km, 30 km, 10 km, 3 km and 2 km on maps in geographical detail. The method allows to model more detailed transformations of the flow at other intermediate depths.